Asymmetry of the insula‐sensorimotor circuit in Parkinson's disease. (6th September 2021) - Goelman, Gadi; Dan, Rotem; Růžička, Filip; Bezdicek, Ondrej; Jech, Robert
Abstract: Patients with Parkinson's disease (PD) experience motor and non‐motor symptoms, suggesting alterations of the motor and/or limbic system or more probably of their communications. We hypothesized that the communication between the insula (part of the limbic system) and sensorimotor cortex in PD is altered and hemispheric asymmetric. Furthermore, that this asymmetry relates to non‐motor symptoms, and specifically, that apathy‐related asymmetry is unique to PD. To test these hypotheses, we used a novel multivariate time‐frequency analysis method applied to resting‐state functional magnetic resonance imaging (MRI) data of 28 controls and 25 participants with PD measured in their OFF medication state. The analysis infers directionality of coupling, that is, afferent or efferent, among four anatomical regions, thus defining directed pathways of information flow, which enables the extension of symmetry measures to include directionality. A major right asymmetry reduction of the dorsal‐posterior insula efferent and a slight bilateral increase of insula afferent pathways were observed in participants with PD versus controls. Between‐group pathways that correlated with mild cognitive impairments combined the central‐executive and default‐mode networks through the right insula. Apathy‐correlated pathways of the posterior insula in participants with PD versus controls exhibited reduced right efferent and increased left afferent. Because apathy scores were comparable between the groups and effects of the other motor and non‐motor symptoms were statistically removed by the analysis, the differences in apathy‐correlated pathways were suggested as unique to PD. These pathways could be predictors in the pre‐symptomatic phase in patients with apathy. Abstract : (Top) Apathy‐associated multinode directed pathways of the insula. Pathways are asymmetric with 65% dorsal‐posterior efferent in the right hemisphere and 35% dorsal‐posterior afferent in the left hemisphere. These pathways were shown to be unique to PD and thus can be predictors in the pre‐symptomatic phase for subjects with apathy. (Bottom) MCI‐associated directed pathways, combining the central‐executive and the default‐mode networks through the right insula. These were not unique to PD.